The Effect of Progressive Muscle Relaxation Therapy on Elderly's Sleep Quality at PSTW Budi Luhur, Kasongan, Bantul - ., Istichomah; ., Rika Monika; Theresia, Firmina; Miftahul Khoeriyah, Salis; Satria, Nanda (KnE Social Sciences, 2023)
The sleep pattern of the elderly is different from that of the young. There are four sleep phases in which young people can enter a deep sleep phase, while the elderly experience a decreased sleep phase as a result of poor sleep, meaning that the elderly tend to be restless and easily awakened, which can interfere with sleep quality. The elderly have memory disorders and emotional disorders that reduce their quality of life. This paper was quantitative research that used a pre-experimental research design with pre-test and post-test with a control group. The results of the study obtained a sig. (2-tailed) value of 0.000 or 0.05. There was a difference in the average PSQI score in the pre-test and post-test measurement of the intervention group, while in the control group the sig. (2-tailed) value was 0.020 or 0.05. There was no difference in the average PSQI score in the pre-test and post-test measurements of the control group. Progressive muscle relaxation is an alternative therapy that serves to reduce muscle tension, which can then relax muscles ranging from facial muscles to leg muscles. There was an effect of progressive muscle relaxation therapy on the sleep quality of the elderly in the intervention group at PSTW Budhi Luhur Kasongan Bantul. Keywords: Progressive Muscle Relaxation Therapy, Elderly, Sleep Quality